Postcolonial Digital Learning in Ghanaian Art Education: Between Technology, Memory, and Cultural Survival - Daitey William (International Journal of Education and Digital Learning (IJEDL), 2025)
This study examines the intersection of digital learning, postcolonial identity, and cultural survival within Ghanaian art education in the contemporary technological era. The rapid expansion of digital technologies and artificial intelligence has significantly transformed educational systems worldwide, including in Ghana. However, the integration of digital learning into African educational contexts raises important concerns regarding epistemic coloniality, indigenous knowledge marginalization, and the preservation of cultural memory. This article aims to critically analyze how digital learning simultaneously functions as a mechanism of educational modernization and a site of cultural negotiation within postcolonial societies. The study employs a qualitative conceptual approach grounded in postcolonial theory, decolonial epistemology, cultural memory studies, and indigenous knowledge frameworks. Rather than relying on quantitative data, the research utilizes critical interpretive analysis of scholarly literature related to digital pedagogy, African art education, artificial intelligence, and cultural preservation. The analysis focuses on the relationship between technology, memory, representation, and indigenous artistic traditions within Ghanaian educational transformation. The findings indicate that contemporary digital learning systems often reproduce Western epistemological dominance through standardized technological infrastructures, algorithmic representation, and culturally selective educational content. Indigenous Ghanaian artistic traditions—including oral storytelling, Adinkra symbolism, ritual performance, and communal artistic learning—frequently remain underrepresented within digital educational environments. Nevertheless, the study also reveals that digital technologies possess significant potential for preserving cultural heritage, expanding indigenous visibility, and developing innovative pedagogical practices when implemented through culturally responsive and decolonial frameworks. The article concludes that the future of Ghanaian art education depends on reconstructing digital learning models grounded in epistemic plurality, indigenous aesthetics, and cultural sovereignty. Digital learning should not merely serve technological modernization but also function as a medium for sustaining collective memory, artistic identity, and postcolonial cultural resilience. This study contributes to contemporary discussions concerning decolonial education, digital pedagogy, and the ethical implications of artificial intelligence within indigenous educational contexts.